Commmunity Perception of Gender Equality in Families in Lattekko Village, Bone Regency - Atma Ras; Musrayani Usman; Nuvida RAF; Arsyad Genda; Mario Mario; Dimas Ario Sumilih; Hariashari Rahim; Andi Nurlela; Feby Awaliyah (International Journal of Social Science and Humanity, 2024)
Gender is a cultural interpretation and receives a lot of attention in society. One of the problems that occurs in the community in Lattekko Village, Bone Regency, this research is to determine community perceptions and forms of equality within the family by studying family systems theory through developing scales or indicators that reflect aspects of gender equality. Quantitative approach to data collection. The research results show that the level of public knowledge regarding gender equality is still very low. Of the total 40 respondents, only 9 (22.5%) respondents knew gender, while 31 (77.5%) respondents did not know. However, the level of gender equality between men and women does not result in differences in treatment, work, time, public participation in society and household duties. The level of knowledge of respondents regarding gender equality in Lattekko Village, Awangpone District, Bone Regency, is still very low.